Induction of Viable but Nonculturable Escherichia coli O157:H7 by Low Temperature and Its Resuscitation - Wei, Caijiao; Zhao, Xihong (Frontiers in Microbiology, 2018)
Low temperature refrigeration is the most common way of food preservation. While Escherichia coli O157: H7, like many other pathogenic bacteria, can be induced into a viable but nonculturable (VBNC) state by incubation at low temperature in adverse environments. Therefore, the aim of this study was to explore that the E. coli O157: H7 survival strategy at 4°C and -20 °C with different condition. Under low temperature, the initial inoculum of 2.1×107 CFU/mL E. coli O157:H7 cells were induced into the VBNC state in normal saline, distilled water, LB broth at -20°C after 176, 160, 80 days respectively. After adding Tween80 at 37°C E. coli O157:H7 cells could regain the ability to divide. Overall, our data indicate that E. coli O157: H7 can be induced into VBNC state having active in metabolism, and can recover from their dormant state, becoming fully culturable. To better understand the risk associated with VBNC cells, further investigations are necessary for risk assessment in food safety and public health.